2012
DOI: 10.1007/s11144-012-0522-5
|View full text |Cite
|
Sign up to set email alerts
|

Propan-2-ol dehydration on H-ZSM-5 and H-Y zeolite: a DFT study

Abstract: The catalytic dehydration of propan-2-ol over H-Y and H-ZMS-5 aluminated\ud zeolite models, mimicking both internal cavities and external surfaces, was\ud studied by DFT calculations to investigate the reaction mechanism. After the adsorption of propan-2-ol on the zeolite, the dehydration mechanism starts with alcohol protonation, occurring by one acidic –OH group of the zeolite fragment, followed by a concerted b-elimination to give propene. The catalytic activity is\ud affected by the size of the zeolite cav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…Some structures of purely silicic surfaces were proposed for BEC, LTL, and LTA [22] (with Si/Al=∞ or 1, Na or Ca form, for the latter), for the sake of comparison by using high‐resolution electron microscopy. Cluster models of the external surface of ZSM‐5 were used recently for reactivity purposes (butene isomerization or propanol dehydration) but again without any systematic investigation of the location of protons . Al−OH and Si−OH were invoked at the surface, the latter of which had a higher reactivity for butene isomerization .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some structures of purely silicic surfaces were proposed for BEC, LTL, and LTA [22] (with Si/Al=∞ or 1, Na or Ca form, for the latter), for the sake of comparison by using high‐resolution electron microscopy. Cluster models of the external surface of ZSM‐5 were used recently for reactivity purposes (butene isomerization or propanol dehydration) but again without any systematic investigation of the location of protons . Al−OH and Si−OH were invoked at the surface, the latter of which had a higher reactivity for butene isomerization .…”
Section: Introductionmentioning
confidence: 99%
“…Al−OH and Si−OH were invoked at the surface, the latter of which had a higher reactivity for butene isomerization . For propanol dehydration, only surface bridging OH groups were considered, which had enhanced adsorption properties but hindered reactivity compared to that of the bulk.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, one cannot disregard the possibility of an alternative reaction mechanism for the latter case. A recent DFT study by Prestianni et al [25] indicated a concerted E2 b-elimination mechanism for the dehydration of 2-propanol on H-ZSM-5 and H-Y zeolite.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol dehydration has been extensively used as a probe reaction to characterize acidity in zeotype materials, 6,[35][36][37][38] and recent computational as well as experimental studies have led to detailed understanding of underlying reaction mechanisms and pathways of light (C1-C4) alcohol dehydration on solid acid catalysts. 37,[39][40][41][42][43][44][45][46][47] The ubiquitous themes tying these studies together are: (i) the evidence for the coupling of unimolecular and bimolecular dehydration pathways, where adsorbed dimers that produce di-alkyl ethers (bimolecular dehydration product) can also contribute to olefin formation (unimolecular dehydration product), 43,44 (ii) inhibition of olefin formation rates at high alcohol partial pressures (> 50 torr) due to the higher stability of adsorbed alcohol dimers relative to monomers, 37,39 and (iii) an increased preference to unimolecular dehydration with increasing temperatures. 37,39,43,44 The favorability of E1/E2 elimination pathways during alcohol dehydration on zeolites depends on the stability of carbenium formed during the prominence of E2 type pathways as the RDS for isopropanol (a secondary alcohol) dehydration in aluminosilicates MFI, 41,48 and FAU, 41 while primary alcohol dehydration primarily occurs through E1-type elimination pathways.…”
Section: Isopropanol Dehydration On P-zeosilsmentioning
confidence: 99%